The effort to enhance pupils cognitive learning achievement using contextual teaching and learning approach - Bhure, Milburga; Welu, Felix; See, Siprianus; Ota, Maria Kristina (Journal of Research in Instructional, 2021)
Contextual teaching and learning (CTL) become learning that can empower pupils' cognitive learning achievement. The research objective was to enhance pupils' cognitive learning achievement (CLA) using the CTL approach. The classroom action research by Kemmis and McTaggart was used in this research. The subjects of this study were pupils of grade IV SDK Doreng, Doreng District, Sikka Regency. Participant research was ten pupils' (three boys, seven girls). Ten multiple-choice tests were used for the evaluation of each cycle. Analysis of data was quantitatively and percentage—five categories for student CLA. The success indicator is based on a score of 65 and classical completeness of 85%. The results showed that the activity of pupils and teachers in the first cycle was low. This finding was followed by not achieving completeness, where only 70% of pupils completed. The second cycle findings inform that pupils' and teacher activities were excellent, followed by classical completeness, reaching 100%. This action research concludes that CTL can improve pupils' CLA. This research recommends using CTL in the future to enhance pupils' CLA.